Changes in the blood cyclosporine level after switching from voriconazole to isavuconazole in a patient with aplastic anemia: insights from physiologically based pharmacokinetic model simulation and the Adverse Event Reporting System database study - Shiraishi, Chihiro; Kato, Hideo; Ino, Kazuko; Iwamoto, Takuya (Frontiers in Microbiology, 2025)
IntroductionIsavuconazole, a broad-spectrum triazole approved by the United States Food and Drug Administration (FDA) in 2015, moderately inhibits cytochrome P450 3A4. Although antifungal agents are often used concomitantly with cyclosporine, the effect of switching from voriconazole to isavuconazole on the blood cyclosporine level remains unclear.CaseA 63-year-old Japanese male was administered oral cyclosporine (10:00 and 21:00) for severe aplastic anemia. Following pneumonia with positive Aspergillus antigen and an elevated β-D-glucan level, antifungal therapy was initiated. After switching from voriconazole (10:00 and 21:00) to isavuconazole (approximately 08:00), the blood cyclosporine level decreased by more than half. Although the blood cyclosporine level decreased after switching to isavuconazole, the dose of cyclosporine was not increased because of its possible effect on renal function. Considering the inhibitory effects on the gastrointestinal tract, a physiologically based pharmacokinetic analysis estimated that isavuconazole increased the area under the curve (AUC) and Cmax of cyclosporine by 1.48-fold and 1.84-fold, respectively, although assuming no change in gastrointestinal metabolism, these effects were minimal. For interaction with voriconazole considering gastrointestinal metabolism, the predicted increases in AUC and Cmax were 3.74-fold and 3.86-fold, respectively. The FDA Adverse Event Reporting System database included 9,144 reports on cyclosporine and 174 on cyclosporine with voriconazole, but none concomitant with isavuconazole. The reporting odds ratios for cyclosporine and isavuconazole could not be assessed because of insufficient reports.ConclusionThe interaction of isavuconazole with cyclosporine was weaker than that with voriconazole. Maintaining a two-hour dosing interval between isavuconazole and cyclosporine may minimize gastrointestinal drug interactions.